Effective Communication Between The Coach And Tunas Muda Bengkulu Team In Building Good Relationships - Karim, Zuhri Abdul; Putra, Dilmai; Dianthi, Martha Heriniazwi (Universitas Dehasen Bengkulu, 2025)
Effective communication is the process of delivering messages precisely so that they can be clearly understood by the message recipient. In various contexts, both personal and professional, effective communication plays a significant role because it can influence the outcomes of interactions and relationships between individuals. The purpose of this research is to understand effective communication between coaches and Tunas Muda Bengkulu Team in building good relationships. This research is of qualitative type. The theory used is the theory of effective communication according to Devito. The results of this study indicate that, first, openness: the coach of Tunas Muda Bengkulu Team prioritizes open, clear, and supportive communication, which helps build trust and create a collaborative atmosphere within the team. Second, empathy: the coach builds effective communication through an open and honest approach, listening to the players' problems and hopes. Third, supportive attitude: the coach supports the team's morale, especially in difficult situations, by providing clear directions and motivational words, helping the team stay focused and enthusiastic. Additionally, support from teammates, who strengthen each other, enhances a positive atmosphere and builds the team's mental strength to face challenges on the field. Fourth, a positive attitude: the coach gives constructive criticism in a supportive manner, beginning with appreciation for the players' efforts to maintain their spirit. Fifth, equality: in the relationship between coach and players, fair treatment does not always mean the same treatment for everyone. The coach may give more attention to players who have important roles in the team's strategy, but this is done for the overall interest of the team, not favoritism. Thus, effective communication between the coach and Tunas Muda Bengkulu Team in building good relationships can serve as a reference for the application of effective communication theory according to Devito.